MICROBIAL CONTAMINATION STANDARD OF PEGAGAN LEAVES SAMPLE AS QUALITY REQUIREMENTS FOR RAW MEDICINAL PREPARATIONS - Sudimartini, Luh Made; Putranto, Genta Dhamara Adam; Suarjana, I Gusti Ketut; Merdana, I Made (Buletin Veteriner Udayana, 2022)
Pegagan is an excellent plant used as a raw material for traditional medicine. The bioactive content in pegagan leaves plays a role in the wound healing process, able to cure complex dermatitis in dogs, proven as neuroprotective, and can reduce oxidative stress of body cells. Many efficacies make pegagan leaves have the potential to be produced into various forms of medicinal preparation. This study will calculate the number of microbes’ contamination in pegagan leaves which will be used as various drug preparations and then compare it to the General Standard Parameters for Medical Plant Extracts of the Ministry of Health of Republic Indonesia in 2000 and Regulation of the Head of BPOM RI Number 32 of 2019. The examination of microbial contamination was carried out through the Total Plate Count and Yeast Fungus Test. The research data obtained were quantitative data that were analyzed by counting the number of microbes that grow on PCA and PDA after incubation at the appropriate growth temperatures. The results of this study show that the Total Plate Count from the sample was 3250 CFU/gr and the Yeast Fungus Test was 450 CFU/gr. The number of Total Plate Count has fulfilled the requirements for the Oral Drugs (£10 5 colony/gr) and required for Semi Solid Drugs (£10 7 colony/gr). The number of Yeast Fungus Test are required for Oral Drugs (£10 3 colony/gr) and required for Semi Solid Drugs (£10 4 colony/gr).